Urban accessibility and spatial segregation in Brazilian cities: A configurational perspective - Ana Paula Barros; Valério Augusto Soares de Medeiros; Maria da Piedade Morais (Institute for Applied Economic Research (ipea), 2017)
This article investigates the use of the configurational variable, which deals with the city form-space relations regarding transportation issues, to study spatial segregation and urban accessibility in four Brazilian cities (Belém, Manaus, Recife and S\~ao Paulo), with a focus in precarious settlements and in the location of social classes in the urban space and their relative degree of accessibility/integration to the city as a whole. The study searches to verify to what extent such settlements are more segregated/isolated in the urban fabric as compared to the other areas of the city. For this purpose, we have used the classification of census tracts prepared by the Centro de Estudos da Metrópole (CEM) of the Ministry of Cities of Brazil (Marques et al. 2007), based upon data from the 2000 demographic census of the Brazilian Census Bureau (IBGE, 2003), as well as axial maps of these cities, according to the methodological tools of the Theory of the Social Logic of Space, also known as Space Styntax, which allows quantifying the configurational variable by means of the so-called "integration value". The confrontation of the information, organized on a Geographical Informational System (GIS), has underpinned a series of interpretations over the existing process of "voluntary" and "involuntary" segregation in such cities, highlighting the importance of the configurational variable for urban studies of such nature.
Keywords: R14; R20; R31; R38; R40; Z13; 330; urban mobility; space syntax; spatial segregation; urban accessibility; integration